The Political Movement of the Muhammadiyah Youth Exponent in Supports the Precident and Vice Precident Candidates in the General Election - Prakoso, Velandani; Alfarabi, Misran; Alhamdi, Ridho (Politicon : Jurnal Ilmu Politik, 2022)
This research focuses on the political movement strategy carried out by young Muhammadiyah exponents who have gathered in the Progressing Indonesia House (RIB) and the Indonesian Pencerah Alliance (API). Young Muhammadiyah exponents in this case are young Muhammadiyah cadres who have attended the cadre process and structurally have served in Muhammadiyah autonomous organizations. Â In reading the strategies of the political movement, a theoritical framwork is used, namely the structure of political opportunities, mobilization of resources, and framing of collective action. This study uses a descriptive qualitative approach and the analysis uses the Nvivo 12 Plus software. The research data were obtained from the results of interviews, document studies, and previous research which were related to each other. The results of this study indicate that young Muhammadiyah cadres realize that the Muhammadiyah Association is currently increasingly occupying a strategic position, both in its existence and as a strategic partner of the government. The growth and development of this awareness has spurred the construction of strategic, tactical, and futuristic thinking amidst many strategic choices and political articulations. The emergence of a political movement in the 2019 presidential election which was initiated by Muhammadiyah young exponential cadres is proof that there is a polarization that occurs in Muhammadiyah young cadres and indirectly becomes a fighting arena for cadres who are diaspora in the realm of national politics.